2007
DOI: 10.1007/s11144-007-5203-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of palladium catalyst deactivation in synthesis of 4,10-diformyl-2,6,8,12-tetraacetyl-2,4,6,8,10,12-hexaazaisowurtzitane

Abstract: Polycyclic nitramine hexanitrohexaazaisowurtzitane (HNIW, CL-20) is synthesized via hydrodebenzylation of a precursor over palladium-based catalyst.In the present work, we studied the influence of the synthesis method of the palladium-based catalyst on the catalyst behavior during the hydrodebenzylation reaction of 2, 4,6,8,10,12-hexabenzyl-2,4,6,8,10,12-hexaazatetracyclo[5.5.0.0 3,11 .0 5,9 ] dodecane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 4 publications
1
5
0
1
Order By: Relevance
“…, 1 → 2 and 1 → 2 → 3 . Similarly, it can be found that the used catalysts were easily deactivated for hydrogenolysis of HBIW as reported. Surprisingly, the Pd/TiO 2 -2 can be recycled for only TADBIW hydrodebenzylation ( 2 → 3 ).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…, 1 → 2 and 1 → 2 → 3 . Similarly, it can be found that the used catalysts were easily deactivated for hydrogenolysis of HBIW as reported. Surprisingly, the Pd/TiO 2 -2 can be recycled for only TADBIW hydrodebenzylation ( 2 → 3 ).…”
Section: Resultssupporting
confidence: 68%
“…The cleavage of the C–N bond via hydrogenolysis is one of the most frequently used deprotecting classifications for amino functionalities with benzyl groups in the fields of fine chemistry as well as pharmaceuticals and the military. The hydrogenolysis reactions are commonly based on heterogeneous Pd-based catalysts. However, some significant problems for practical application often appear, such as low yields for some special debenzylation reactions, , a high precious metal loading and usage amount, and poor stability. Varieties of Pd particle catalysts have to be explored in order to improve the cost efficiency of debenzylation processes, such as Pd particles supported on different carbons, , Pd/Al 2 O 3 , Pd/In 2 O 3 , Pd/SiO 2 , Pd/DOWEX, and others. , Recently, Ananikov et al reported that Vulcan XC-72 carbon carried 1 wt % Pd particles disclosed with a high turnover number (TON) up to 5000 with a low usage amount of only 0.02–0.3 mol % of Pd for the transfer hydrodebenzylation system with HCO 2 H as the reductant. From the viewpoint of practical applications, development of more cost-effective Pd catalysts is still an attractive topic to debenzylation.…”
Section: Introductionmentioning
confidence: 99%
“…Стадия восстановительного дебензилирования вносит наиболее значимый вклад в стоимость ГАВ. Катализатор подвергается отравлению продуктами дебензилирования и требует частой замены [15].…”
Section: рис 1 синтез гав через трансформацию гбunclassified
“…TADF) have been reported. 619,620 The studies concerned the effects of the preparation procedure of heterogeneous catalysts, components of the reaction mixture and process conditions on the catalyst stability against deactivation in the catalytic debenzylation. Using modern methods of analysis, the authors established the optimal degree of dispersion of Pd on the support surface for debenzylation.…”
Section: Scheme 149mentioning
confidence: 99%